Potential benefit in information providing and influence on patient anxiety and satisfaction by means of preoperative explanatory videos in total extraperitoneal inguinal hernioplasty: study protocol of a multicentre, double-blinded, randomised parallel-group controlled trial. Issue 1 (26th January 2021) - Lunger, Fabian; Frank, Florian; Peros, Georgios; Lunger, Alexander; Vuille-dit-Bille, Raphael; Guglielmetti, Laura; Breitenstein, Stefan; Grieder, Felix; Ehlers, Jan; Gingert, Christian
Abstract : Introduction: The use of electronic media in informed consent giving has become increasingly important in recent years. Due to the easy access to information via electronical media, patients are primed in a heterogeneous manner concerning expectations and wishes regarding surgical interventions. Inherent to its nature elective interventions are critically questioned as there is time for information gathering and reflection. In this study, we set out to investigate the effect of an educational video as a supporting element in the process of informed consent giving for one the most frequently performed interventions in general surgery, namely inguinal hernia repair. Methods and analysis: In a multicentre setup, eligible patients for primary inguinal hernia repair will be randomly assigned to one of three groups. All three groups will have a preoperative informed consent discussion with a physician in which they will eventually sign the informed consent sheet if participation is desired. Eventually, all three groups will get an online link. For two groups, the link will lead to a video with audiovisual information (an inguinal hernia video for the intervention group and a mock video for the control group). The intervention video provides basic principles of endoscopic extraperitoneal hernia repair. The second video is similar in length and design and displays general aspects of day surgery in the two study centres. All the three study groups will be provided with a copy of the informed consent form as it is standard by now. The third group's link will lead to the digital version of the informed consent brochure. Primary outcomes will consist of (1) score in a multiple choice test assessing gain of knowledge regarding hernia repair, (2) difference in the State-Trait Anxiety Inventory and (3) patient satisfaction questionnaire Individual Clinician Feedback (ICF, Picker Institute, Germany) as assessed 1–2 days after the first consultation. The study design guarantees double blinding, there will be no unblinding at any point. All patients will receive the same, quality and number of medical consultations as well as in the same surgical treatment. (Minor differences in the total extraperitoneal technique of the surgical treatment due to anatomical or pathophysiological differences are independent of the group allocation). Except for the additional videos, there will be no difference in in the information provided and the treatment prior, during or after the hernia repair. Ethics and dissemination: We plan to publish the study in a peer-reviewed journal. The proposed research project has been reviewed by the Cantonal Ethics Committee (BASEC-No 2020–01548). In accordance with national legal regulations in Switzerland stated by the Human Research Act, the proposed project was declared exempt from approval requirement. Trial registration number: NCT04494087; Pre-results .